Decision Support System Appointment Of Permanent Employees With Analytical Hierarchy Process Method - M. Ajis Akbar Kurniawan; Siswanto, Siswanto,; Jhoanne Fredricka (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2022)
The appraisal system for the appointment of training employees to permanent employees at Rakyat Bengkulu Television (RBTV) has not been computerized and is still done manually through an assessment form that has been provided to give each training employee a score that has been seen for the last 3 months. This takes a long time to find out who is eligible to be appointed as permanent employees. The Decision Support System for the appointment of permanent employees at the Bengkulu Rakyat Televisi (RBTV) Bengkulu was made using the Visual Basic .Net programming language and SQL Server 2008r2 database, where in the application one of the Decision Support System Methods, namely Analytical Hierarchy Process (AHP) has been applied. This Decision Support System for the appointment of permanent employees at the Bengkulu Rakyat Televisi (RBTV) Bengkulu can assist the employee appraisal process and provide recommendations for those who are eligible to be appointed as permanent employees. As for the test results in 2018 using the AHP Method, it was found that 3 employees had the highest scores out of 10 employees, namely Galeh Fajar (87.81), Retno Setiawan (85.57), and Richo Rieo (85.5).